Early Postnatal Development of Reciprocal Ia Inhibition in the Murine Spinal Cord - Wang, Zhi (American Physiological Society, 2008)
The pathway mediating reciprocal inhibition from muscle spindle afferents (Ia axons) to motoneurons (MNs) supplying antagonist muscles has been well studied in adult cats, but little is known about how this disynaptic pathway develops. As a basis for studying its development, we characterized this pathway in mice during the first postnatal week, focusing on the projection of quadriceps (Q) Ia axons to posterior biceps-semitendinosis (PBSt) MNs via Ia inhibitory interneurons. Synaptic potentials in PBSt MNs evoked by Q nerve stimulation are mediated disynaptically and are blocked by strychnine, implying that glycine is the major inhibitory transmitter as in adult cats. The specificity of neuronal connections in this reflex pathway is already high at birth; Q afferents evoke inhibitory synaptic potentials in PBSt MNs, but afferents supplying the adductor muscle do not. Similar to this disynaptic pathway in cats, Renshaw cells inhibit the interposed Ia interneurons, as they reduce the disynaptic input from Q axons but do not inhibit PBSt MNs directly. Reciprocal inhibition functionally inhibits the monosynaptic excitatory reflex in PBSt MNs by P3, but this functional inhibition is weak at P1. Finally, deletion of the transcription factor Pax6, which is required for the development of V1-derived Renshaw cells, does not block development of this pathway. This suggests either that Pax6 is not required for the phenotypic development of all V1-derived spinal interneurons or that these inhibitory interneurons are not derived from V1 precursors.